Ekonomické aspekty inovace v podniku - Suhareva, Elizaveta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Předmětem bakalářské práce “ Ekonomické aspekty inovace v podniku” je popsat procesní inovace a zavedení nových služeb v podniku. V teoretické části práce jsou vysvětleny pojmy o podniku, inovace a její efektivnost, a základní ukazatele finanční analýzy. Analytická část práce popisuje inovace vybrané společnosti a možnosti jejího financovaní. Výhody a nevýhody zavádění inovací v podnicích.

The subject of the bachelor's thesis "Economic aspects of innovation in a company" is to describe process innovation and the introduction of new services in a company. In the theoretical part of the work, concepts about the company, innovation and its effectiveness and basic indicators of financial analysis are explained. The analytical part of the work describes the innovations of the selected company and the possibilities of its financing. Advantages and disadvantages of introducing innovations in enterprises.
Economic Aspects of Innovation in an Enterprise
Keywords: Podnik; inovace; konkurenceschopnost; procesní inovace; financovaní; analýza.; Company; innovation; Competitiveness; process innovation; financing; analysis.